DOMINICAN CHURCH IN CHORTKIV: GEOLOGICAL CONDITIONS, THE CRYPT GEOMETRIZATION, THE BUILDING STABILIZATION - Kuzmenko, Е.; Maksymchuk, V.; Chepurnyi, І.; Bagriy, S.; Romaniuk, О.; Kuderavets, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article is devoted to the results of geological and geophysical research conducted on the territory of the Dominican Church in Chortkiv, Ternopil region to determine the stress-strain state of building elements and search for voids and compaction zones in the subsurface soil layer. Research methods were methods of natural pulsed electromagnetic field of the Earth, vertical electric sounding, natural electric potentials, radio wave acoustic profiling, and georadar sounding. The reasons for the development of dangerous processes that negatively affect the condition of the church building are identified and analyzed. It is established that the causes of these deformations are the geological structure of the rocks on which the church is built, the slope of the terrain, natural soil moisture, heavy traffic and the creation of additional sources of water infiltration.
Keywords: engineering-geological conditions; stress-strain state; geophysical researches; deformations; archeology